Evaluation of vertical stress distribution in field monitored GRS-IBS structure. Issue 4 (5th August 2020) - Gebremariam, F.; Tanyu, B. F.; Christopher, B.; Leshchinsky, D.; Han, J.; Zornberg, J. G.
Abstract : This paper presents a case study of a geosynthetic-reinforced soil (GRS) integrated bridge system (IBS) in which the vertical stresses during and after construction were monitored via instrumentation. The purpose of the study was to evaluate the effects of reinforcement spacing, width of the beam seat, and seasonal variations on the vertical stresses measured in the field. The stress distribution observed in the field was also compared to the theoretically estimated stress distribution. The results showed that the bearing bed where the reinforcements are doubled is effective in reducing the applied stresses by about 1.8 to 5.4 times. The width of the beam seat controlled the magnitude of the applied stresses on the GRS abutment and the applied stress was vertically transferred all the way to the foundation level even in wider beam seats. A comparison between field recorded and theoretical stress values showed that the Boussinesq method provides a better estimate of the field vertical stress distribution than the approximate 2 : 1 method, although the 2 : 1 method provides more conservative stresses to be considered for design. Results from long-term monitoring indicated that vertical stress distribution in the GRS abutments was not significantly influenced by seasonal variations.